Revealing the microstructure of metals using ion-irradiation - Yang, Simeon Enjing (2019)
Metallography is concerned with finding the ideal surface processing conditions to reveal the microstructure of metals. Ion etching is one such technique, but its applications have been limited mostly to polishing and grain contrasting. Little study has been done to test if an ion irradiated surface is able to give us meaningful information about the underlying microstructure. The objective of this project is to use low energy ion irradiation to achieve both grain contrast and the obtaining of grain information - visible through simple optical microscopy. A Faced Centred Cubic Copper-Nickel sample was polished, ion irradiated, and its reflectance properties studied. We observe a strong correlation between regions with high optical reflectance and (100) oriented grains, allowing us to potentially infer such orientation in similar alloys without the need for an extensive EBSD scan. This will allow for larger volume microstructural analysis while remaining simple to process. The characterization of the ion irradiated surface presented here also serves to facilitate better understanding of this technique’s impact on metal surfaces for future studies in the field.